MARINE FICOLOGICAL FLORA OF URUBUQUEÇABA ISLAND AND WIZARD STONE. - Fernandes, Sidney; Ana Luiza Santos Silva (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2019)
This paper aims to survey the ficologica flora of marine benthic algae Urubuqueçaba Island and the Stone Sorceress, the first, located on the border between Santos and São Vicente and the second located on the beach of Itarare in Sao Vicente. The Urubuqueçaba Island is located east of the island of São Vicente, in José Menino beach, near the border with the municipality of São Vicente. Near the island, in the south, it is the border between the municipalities of Santos and São Vicente. The island marks the beginning of Itararé beach, which is also the Stone Sorceress, close to it, when the low tide, can be reached on foot. The island is part of the Atlantic, coconut palms are found, fig trees, jerivás, pitangueiras and algae. The fauna found clams, anemones, urchins, turtles, crustaceans, fish such as sea bass, grouper and dory. Besides vultures, cormorants, boobies, herons and gulls. The island, which has 2000 m2 of plateau and is 260 m away from the coast, has a sandy and rocky slope. The Urubuqueçaba Island has triangular shape and not rounded like most islands. The Stone Witch is a boulder located on the beach of Itarare in Sao Vicente, visible Urubuqueçaba Island. The following taxa were identified: Amphiroa rigida, Bryocladia thyrsigera, Centroceras clavulatum, Ceramium brevizonatum, Chaetomorpha antenina, C. spiralis, Gayralia brasiliensis, Grateloupia filicina, Gymnogongrus griffithsiae, Plocamium cartilagineum, Polysiphonia atlantica, Pterocladiella bartlettii, Rhizoclonium africanum, R. riparium, Ulva clathrata, U. fasciata, U. flexuosa, U. intestinalis, U. lactuca e U. rigida.